EEG Assessment in Patients With Disorders of Consciousness: Aims, Advantages, Limits, and Pitfalls - Rossi Sebastiano, Davide; Varotto, Giulia; Sattin, Davide; Franceschetti, Silvana (Frontiers in Neurology, 2021)
A brief review of literature data and results of personal experiences will be primary devoted in defining those procedures that can be carried out on the patient's bed, based on the experience and appropriate training of the examiners, by means of sufficiently simple EEG-polygraphic arrangement . These include EEG, with common electrode array, and sleep evaluation More complex, analytical techniques, such are applications of mathematical algorithms on EEG signals, with information arising from literature and personal data, will be briefly discussed with the aim of defining what type of consistent markers may add information suitable for clinical use or for to better understanding the complex patient condition. The general aim of the advanced analytical techniques will that of detecting the relevant data required to evaluate patients, predict outcome; these data are prone to strongly developing in the next future